The journey towards dollarization: The role of the tourism industry - Ibrahim Dolapo Raheem; Kazeem Bello Ajide (African Governance and Development Institute (AGDI), 2021)
There has been an increasing wave of globalization since the turn of the millennium. This study focuses on two by-products of globalization: dollarization and tourism. Empirical studies have ignored the possible relationship between dollarization and tourism. However, we hypothesize that a booming tourism industry will fuel increase in the usage and circulation of foreign currencies. The objective of this study is to examine the extent to which the tourism industry exacerbates the dollarization process of selected Sub-sahara African (SSA) countries. Using Tobit regression, we found that tourism positively affects dollarization. This result is robust to: (i) alternative measures of tourism; (ii) accounting for endogeneity and outlier effects.
Keywords: C11; E41; F31; 330; Dollarization; Tourism; Sub-saharan Africa